2015
DOI: 10.1007/s40472-015-0054-9
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-Derived Suppressor Cells in Transplantation

Abstract: Myeloid-derived suppressor cells (MDSC) are cells of myeloid origin with enhanced suppressive function. They are negative regulators of the immune responses and comprise a heterogeneous mixture of immunosuppressive cells of monocytic (M-MDSC) and granulocytic (G-MDSC) origin. A more recent nomenclature proposes the term “suppressive monocyte derived cells” (suppressive MCs) to define CSF1/CSF2-dependent mouse suppressor cells that develop from common monocyte progenitors (cMoPs) after birth. Here, we review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Recent evidence suggests that macrophages are also important during the induction of transplantation tolerance (5). Presence of graft infiltrating macrophages has been described in long-term surviving transplant recipients and these immunosuppressive macrophages are associated with unresponsiveness to the transplanted organ (6). These suppressive macrophages are characterized phenotypically by their low expression of Ly6C (Ly6C lo or M2) (5).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that macrophages are also important during the induction of transplantation tolerance (5). Presence of graft infiltrating macrophages has been described in long-term surviving transplant recipients and these immunosuppressive macrophages are associated with unresponsiveness to the transplanted organ (6). These suppressive macrophages are characterized phenotypically by their low expression of Ly6C (Ly6C lo or M2) (5).…”
Section: Introductionmentioning
confidence: 99%
“…The observations include a demonstrated increase in both the number and activity of effector T and NK cells along with elevated HLA-DR expression, consistent with other studies 7678 . These findings suggest that MDSC expansion exists as a counter-regulatory mechanism elicited by certain anti-myeloma agents, and suggests concomitant MDSC suppression could be an important strategy to prevent relapse after autologous stem cell transplant and chemoimmunotherapy 79 . Interestingly, dexamethasone potentiates MDSC immunosuppressive effects 80,81 which is considered a mechanism of action for glucocorticoids in the allograft setting 82 .…”
Section: Role Of Mdscs In the Tumor-induced Immunosuppressive Networkmentioning
confidence: 86%
“…(32,33) In our study, we found that regulatory CD4T cells or CD8T cells preferentially resided in the liver rather than in any other tissues including the spleen, lymph node, or PBMC. Interestingly, MDSCs which are known as suppressive regulators of the immune responses, (34) also resided in high numbers in the liver when compared with the spleen, lymph node, and PBMC.…”
Section: Discussionmentioning
confidence: 99%